재가노인 기능상태 평가도구를 이용한 재가노인 사례관리 프로그램의 효과 평가 - 전경자; 이지윤; 윤종률; June, Kyung-Ja; Lee, Ji-Yun; Yoon, Jong-Lull (Journal of Korean Academy of Nursing, 2009)
Purpose: To evaluate the effects of case management using Resident Assessment Instrument-Home Care(RAI-HC) in home health service for older people. Methods: All elders were assessed at baseline and 3 months later using RAI-HC. The change of function in the intervention group was compared with that of a conventional intervention group. Function was measured with Activities of Daily Living(ADL), Instrumental Activities of Daily Living(IADL), Cognitive Performance Scale(CPS), Depression Rating Scale(DRS), Pain and the number of Clinical Assessment Protocols(CAP). Results: Among ninety two elders participated in the program, 59 were allocated to the case management group and 33 to the conventional group. The intervention, home health service by a nurse over a 3 month period, consisted of comprehensive assessment, case conference for care plan, direct care, education and referral, and outcome evaluation. The percent of elders whose function improved in the intervention group was greater than the conventional group for depression(odds ratio [OR]: 10.941, confidence interval [CI]: 2.338-51.206), IADL(OR: 4.423, CI: 1.151-16.999) and the number of CAP(OR: 11.443, CI: 3.805-34.410). Conclusion: Case management was effective for older people in the community. The effect might have resulted from individual, systematic intervention, however, standards of service including eligibility criteria for case management and collaboration of multi-disciplines is required for more effective home health service programs.